About Unusual Diffraction and Thermal Self-Action of Magnetosonic Beam - PERELOMOVA, Anna (Archives of Acoustics, 2022)
The dynamics of slightly diverging two-dimensional beams whose direction forms a constant angle θ with the equilibrium straight magnetic strength is considered. The approximate dispersion relations and corresponding links which specify hydrodynamic perturbations in confined beams are derived. The study is dedicated to the diffraction of a magnetosonic beam and nonlinear thermal self-action of a beam in a thermoconducting gaseous plasma. It is shown that the divergence of a beam and its thermal self-action is unusual in some particular cases of parallel propagation (θ = 0) and has no analogues in the dynamics of the Newtonian beams. The nonlinear attenuation of Newtonian beams leads to their defocusing in gases, whereas the unusual cases correspond to the focusing in a presence of magnetic field. The examples of numerical calculations of thermal self-action of magnetoacoustic beams with shock fronts are considered in the usual and unusual cases of diffraction concerning stationary and non-stationary self-action. It is discovered that the diffraction is more (θ = 0) or less (θ = π/2) manifested as compared to that of the Newtonian beams. The beams which propagate oblique to the magnetic field do not reveal diffraction. The special case, when the sound and Alfvénic speeds are equal, is discussed. This magnetosonic beams incorporate acoustic and Alfvénic properties and do not undergo diffraction in this particular case.